A device and method for testing the wettability of lithium ion electrolyte and battery materials

By designing a test equipment for lithium-ion batteries, and calculating the infiltration radius using a buret tube and an angle measuring instrument, the problem of difficulty in evaluating the infiltration radius in the prior art was solved, and rapid and accurate infiltration measurement was achieved, which promoted the improvement of the performance of lithium-ion batteries.

CN110426322BInactive Publication Date: 2025-03-14HUARUI XINXIANG CHEM
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201910742983.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-08-13
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and accurately evaluate the wetting properties of lithium-ion battery electrolyte on battery materials, resulting in slow improvement in lithium-ion battery performance.

Method used

A device including a test bracket and a burette was designed to inject electrolyte into the battery material through the burette, and the infiltration radius was calculated using an angle measuring device and a scale needle to achieve rapid and accurate measurement of the infiltration property of the electrolyte.

Benefits of technology

The equipment can quickly and accurately measure the wetting properties of the electrolyte on battery materials, shorten the development cycle of electrolyte and battery materials, and improve development efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110426322B_ABST
    Figure CN110426322B_ABST
Patent Text Reader

Abstract

The present invention relates to a device and method for testing the wettability of lithium ion electrolyte and battery materials. The testing device includes a test stand and a burette. The burette can be fixed on the test stand. A surface vessel for placing a test substrate is provided below the burette. The burette is used to drip the electrolyte to be tested onto the test substrate. An angle measuring device and a graduated needle are also provided on the test stand. When the graduated needle points to the outermost part of the electrolyte, the angle value corresponding to the graduated needle can be read by the angle measuring device. The present application can quickly and directly characterize the wettability of the electrolyte. The device has a simple structure, is easy to carry or move, has high measurement efficiency, and has high measurement results with high accuracy and good repeatability. In the process of electrolyte development or battery manufacturing, the electrolyte formula or battery pole sheet rolling process can be quickly optimized according to the measurement results, shortening the development cycle and improving the development or manufacturing efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to lithium battery technology, in particular to a device and method for testing the wettability of lithium ion electrolyte and battery materials. Background Art

[0002] In recent years, environmental pollution problems have become increasingly prominent, and my country has also attached increasing importance to environmental protection issues. The formulation and implementation of policies such as carbon quotas and carbon credits have played a significant role in promoting energy conservation and emission reduction. Policies such as carbon quotas and carbon credits have promoted the development of new energy and accelerated the overall process of new energy industrialization. The development of new energy vehicles has caused lithium-ion batteries to grow exponentially in recent years.

[0003] In lithium-ion battery technology, due to the constraints of positive and negative electrode materials and electrolytes, the growth of lithium-ion battery energy density and performance improvement are slow, which cannot meet the market demand for high-performance lithium-ion batteries. In order to improve the performance of lithium-ion batteries, it is necessary to quickly evaluate the performance of positive and negative electrode materials and electrolytes to improve R&D efficiency; the electrolyte plays the role of transmitting ions between the positive and negative electrodes in lithium-ion batteries. Different electrolyte formulas, positive and negative electrodes with different compaction densities, and separators of different thicknesses have a great impact on the wettability of the electrolyte. How to quickly evaluate its wettability is a major problem that plagues technicians.

[0004] Regarding the detection of electrolyte wettability, the technical solution disclosed in the Chinese patent document with publication number CN101009392A uses visual inspection to observe the wettability of the battery by the electrolyte in the battery after disassembly and injection. This method has many influencing factors and is prone to large errors. The Chinese patent document with publication number CN102866084A discloses "a method for measuring the wettability of battery materials by lithium or lithium-ion battery electrolyte". The positive electrode, negative electrode and diaphragm of the battery are made into sheet samples with smooth and flat surfaces as the test substrate for the electrolyte to be tested, and the half-angle method is used to observe the wettability of the electrolyte on the electrode sheet. This method has high requirements on equipment and a harsh operating environment. Summary of the invention

[0005] The purpose of the present invention is to provide a device and method for testing the wettability of lithium ion electrolyte and battery materials, which is used to conveniently, quickly and accurately measure the wettability of electrolyte to the positive electrode, negative electrode and diaphragm of the battery, thereby shortening the development cycle of electrolyte and battery materials.

[0006] In order to solve the above problems, the present invention provides a device for testing the wettability of lithium ion electrolyte and battery materials, including a test bracket and a burette, wherein the burette can be fixed on the test bracket, and a surface vessel for placing a test substrate is provided below the burette, and the burette is used to drip the electrolyte to be tested into the test substrate. The test bracket is also provided with an angle measuring device and a scale needle, and when the scale needle points to the outermost periphery of the electrolyte, the angle value corresponding to the scale needle can be read by the angle measuring device.

[0007] The device for testing the wettability of lithium ion electrolyte and battery materials provided by the present invention also has the following technical features:

[0008] Furthermore, the angle measuring device is a semicircular protractor with a scale, the center of the protractor is fixed on the bracket and coincides with the central axis of the burette, and the scale needle is fixed at the center of the protractor and can rotate around the center of the protractor.

[0009] Furthermore, it also includes a timer for recording the wetting time after the electrolyte to be tested is dripped into the test substrate.

[0010] Furthermore, the surface vessel is a flat glass vessel.

[0011] The present invention provides a method for testing the wettability of lithium ion electrolyte and battery materials, comprising the following steps:

[0012] The prepared positive electrode, negative electrode or separator is cut into sheet samples as test substrates, and electrolytes of different formulations are prepared according to different solvent ratios as the electrolytes to be tested;

[0013] Use a burette to absorb the electrolyte to be tested, and fix the burette on a test stand; place the test substrate on a surface vessel located below the burette, and adjust the fixed height of the burette on the test stand so that the distance between the lower end of the burette and the upper surface of the test substrate is 0.5CM to 3CM;

[0014] dripping 1 to 5 drops of the electrolyte to be tested onto the test substrate through the burette, starting the timing from the time when the electrolyte to be tested is dripped, and after a preset time, using a graduated needle to point to the outermost edge of the electrolyte, and reading the angle value corresponding to the graduated needle through an angle measuring device;

[0015] The wetting radius is calculated using the sine formula according to the measured angle value corresponding to the scale and the fixed height of the burette on the test support.

[0016] The method for testing the wettability of lithium ion electrolyte and battery materials provided by the present invention also has the following technical features:

[0017] Furthermore, when making the test substrate, electrode sheets with different compaction densities or different thicknesses are selected for the positive and negative electrodes. The positive electrode sheets are vacuum baked at 100℃-120℃ and the negative electrode sheets are vacuum baked at 80℃-100℃ for 6-8 hours, and then cooled to 40℃-60℃ and cut into 2cm*2cm sheet samples for use as test substrates.

[0018] Furthermore, when making the test substrate, the diaphragm selects samples of different surface densities, different thicknesses, different manufacturers or different processes, vacuum bakes them at 60℃-80℃ for 1-4 hours, cools to 40℃-60℃, and cuts them into 2cm*2cm sheet samples as test substrates for standby use.

[0019] Furthermore, the humidity of the test environment is less than 80%.

[0020] Furthermore, the test was repeated at different ambient temperatures.

[0021] The present invention has the following beneficial effects: the present application can quickly and directly characterize the wettability of the electrolyte, the equipment has a simple structure, is easy to carry or move, has high measurement efficiency, and the measurement results are highly accurate and repeatable; in the process of electrolyte development or battery production, the electrolyte formula or battery electrode rolling process can be quickly optimized according to the measurement results, shortening the development cycle and improving development or production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the structure of a device for testing the wettability of lithium ion electrolyte and battery materials according to an embodiment of the present invention;

[0023] Figure 2 Schematic diagram of the principle of the testing method in the embodiment of the present invention. DETAILED DESCRIPTION

[0024] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0025] like Figure 1 , Figure 2In one embodiment of the device for testing the wettability of lithium ion electrolyte and battery materials of the present invention, the device includes a test stand 10 and a burette 20, the burette 20 can be fixed on the test stand 10, a surface vessel 30 for placing a test substrate is provided below the burette 20, the burette 20 is used to drip the electrolyte to be tested into the test substrate, and an angle measuring device 40 and a scale needle 50 are also provided on the test stand 10. When the scale needle 50 points to the outermost periphery of the electrolyte on the surface vessel 30, the angle value α corresponding to the scale needle 50 can be read by the angle measuring device 40, and then the value of the wetting radius R can be quickly calculated according to the angle value α corresponding to the measured scale needle and the fixed height H of the burette 20 on the test stand 10 using the sine formula tanα=wetting radius / fixed height. The device for testing the wettability of lithium ion electrolyte and battery materials in this embodiment has a simple structure, is easy to carry or move, has high measurement efficiency, and has high accuracy and good repeatability of the measurement results.

[0026] In the above embodiment of the present application, preferably, the angle measuring device 40 is a semicircular protractor with a scale, the center of the protractor is fixed on the test stand 10 and coincides with the central axis of the burette 20, and the graduated needle 50 is fixed at the center of the protractor and can rotate around the center of the protractor. Preferably, the device also includes a timer for recording the infiltration time after the electrolyte to be tested is dripped into the test substrate, and the timer can be a stopwatch. Preferably, the surface vessel 30 is a flat glass vessel, and other flat vessels can also be used instead, and the test stand 10 can be a tripod.

[0027] Another embodiment of the present application provides a method for testing the wettability of lithium ion electrolyte and battery materials, characterized by comprising the following steps:

[0028] S100: cutting the prepared positive electrode, negative electrode or separator into sheet samples as test substrates, and preparing electrolytes of different formulations according to different solvent ratios as electrolytes to be tested;

[0029] S200: using a burette to absorb the electrolyte to be tested, and fixing the burette on a test stand; placing the test substrate on a surface vessel located below the burette, and adjusting the fixing height of the burette on the test stand so that the distance between the lower end of the burette and the upper surface of the test substrate is 0.5CM to 3CM;

[0030] S300: dripping 1 to 5 drops of the electrolyte to be tested onto the test substrate through the burette, starting timing from the time when the electrolyte to be tested is dripped, and after a preset time, using a graduated needle to point to the outermost edge of the electrolyte, and reading the angle value corresponding to the graduated needle through an angle measuring device;

[0031] S400: Calculate the wetting radius R using a sine formula (tanα=R / H) according to the measured angle value α corresponding to the scale pin and the fixed height H of the burette on the test stand.

[0032] The present application can quickly and directly characterize the wettability of the electrolyte. The equipment has a simple structure, is easy to carry or move, has high measurement efficiency, and has high measurement results with high accuracy and good repeatability. In the process of electrolyte development or battery production, the electrolyte formula or battery electrode rolling process can be quickly optimized according to the measurement results, shortening the development cycle and improving development or production efficiency. It can be understood that the above test method describes the process of a single test. When multiple repeated experiments are required, certain experimental parameters must be kept consistent in each test. For example, 3 drops of the electrolyte to be tested are dripped into the test substrate each time through a burette. The distance between the lower end of the burette and the upper surface of the test substrate is 1.5CM, that is, the number of drops of electrolyte dripped and the height of the lower end of the burette must be kept consistent in each experiment after determination.

[0033] In the above-mentioned test method of the present application, preferably, when making the test substrate, the positive electrode and the negative electrode are selected from electrode sheets of different compaction density or different thickness, the positive electrode sheet is vacuum baked at 100℃-120℃, and the negative electrode sheet is vacuum baked at 80℃-100℃ for 6-8 hours, cooled to 40℃-60℃, and cut into 2cm*2cm sheet samples as test substrates for standby use. Preferably, when making the test substrate, the diaphragm selects samples of different surface density, different thickness, different manufacturers or different processes, vacuum baked at 60℃-80℃ for 1-4 hours, cooled to 40℃-60℃, and cut into 2cm*2cm sheet samples as test substrates for standby use. Preferably, the humidity of the test environment is less than 80%. This method can measure the wettability of the electrolyte at any ambient temperature. Specifically, during the development of the electrolyte, the test ambient temperature can be -40°C to 80°C. When optimizing the battery manufacturing process, the test ambient temperature can be 10°C to 60°C or selected as needed. The test can be repeated at different ambient temperatures.

[0034] (1) Experimental Example 1

[0035] The test substrate uses a ternary positive electrode material. The positive electrode material components include 97.5% of the active material ternary material (a model of a certain company), 2.0% of carbon black, and 1.5% of the binder PVDF. The raw materials are mixed evenly to prepare a slurry, which is evenly coated on the aluminum current collector, flattened and sliced ​​on a roller machine to make the compaction density 3.45g / cm 3 、3.40g / cm 3 、3.35g / cm 3 、3.3g / cm 3The flattened positive electrode sheet was vacuum dried at 110°C for 8 hours to obtain a substrate to be tested.

[0036] The components and contents of the electrolyte to be tested are: ethylene carbonate 20%, diethyl carbonate 33%, ethyl methyl carbonate 33.5%, LiPF6 12.5%, and vinylene carbonate 1%.

[0037] The wettability determination process is as follows: place the positive electrode test substrate flat on the surface dish, adjust the fixed height of the burette on the test stand to 10CM, and drip 1 drop (about 5μL drop) with the burette at an ambient temperature of 25℃. The height of the lower end of the burette from the test substrate is 0.5cm. The compaction densities are 3.45g / cm 3 , 3.40g / cm 3 、3.35g / cm 3 、3.3g / cm 3 The positive electrode sheet was used as the substrate to be tested. When the electrolyte to be tested was dripped for 30S, the scale needle was pointed to the outermost edge of the electrolyte on the substrate to be tested, and the angle value α corresponding to the scale needle on the angle measuring device was recorded, which were 2°, 4°, 5°, and 9° respectively. The wetting radius R corresponding to each substrate to be tested was calculated using tanα=R / H, which were 3.49mm, 6.99mm, 8.75mm, and 15.84mm respectively.

[0038] From the above test results, it can be seen that when the compaction density of this positive electrode ternary material is lower than 3.35g / cm3, the wetting performance of the electrolyte is greatly improved, which means that this ternary material cannot be used in products with high energy density and high compaction requirements, or the electrolyte used for testing needs to optimize the ratio of different solvents.

[0039] (2) Experimental Example 2

[0040] Preparation of ternary positive electrode test substrate: The positive electrode material components include 97.5% active material ternary material (a model of a certain company), 2.0% carbon black, and 1.5% PVDF binder. The raw materials are mixed evenly to prepare slurry, which is evenly coated on the aluminum current collector, flattened and sliced ​​on a roller machine to make its compaction density 3.35g / cm 3 The flattened positive electrode sheet was vacuum dried at 110°C for 8 hours to obtain a substrate to be tested.

[0041] The electrolyte to be tested is:

[0042] Sample 1: ethylene carbonate 20%, diethyl carbonate 33%, ethyl methyl carbonate 33.5%, LiPF6 12.5%, vinylene carbonate 1%;

[0043] Sample 2: 17% ethylene carbonate, 35% diethyl carbonate, 34.5% ethyl methyl carbonate, 12.5% ​​LiPF6, 1% vinylene carbonate;

[0044] Sample 3: 15% ethylene carbonate, 35% diethyl carbonate, 36.5% ethyl methyl carbonate, 12.5% ​​LiPF6, 1% vinylene carbonate;

[0045] Sample 4: ethylene carbonate 20%, diethyl carbonate 33%, ethyl methyl carbonate 33.3%, LiPF6 12.7%, vinylene carbonate 1%;

[0046] Sample 5: ethylene carbonate 20%, diethyl carbonate 33%, ethyl methyl carbonate 33%, LiPF6 13%, vinylene carbonate 1%;

[0047] Wettability determination: Place the positive electrode test substrate flat in the watch glass, adjust the fixed height of the burette on the test stand, so that the fixed height H of the burette on the test stand is 10CM, and at an ambient temperature of 25°C, use the burette to drip 1 drop (about 5μL droplet), the height of the lower end of the burette from the test substrate is 0.5cm, and use the electrolyte sample 1, sample 2, sample 3, sample 4, and sample 5 to be tested as the electrolyte samples to be tested. When the electrolyte to be tested is dripped for 30S, the scale needle is pointed to the outermost periphery of the electrolyte on the substrate to be tested, and the corresponding angle value α of the scale needle on the angle measuring instrument is recorded, which are 2°, 5°, 7°, 6°, and 8° respectively. Use tanα=R / H to calculate the wetting radius R corresponding to each substrate to be tested, and the wetting radius is 3.49mm, 8.75mm, 12.28mm, 10.51mm, and 14.05mm respectively.

[0048] From the above test results, it can be seen that the compaction density of this ternary material is 3.35g / cm 3 When the electrolyte is used as the electrode, the wettability of different electrolytes is quite different. The electrolyte formulas are compared based on different contents of ethylene carbonate and LiPF6. It is found that with the decrease of ethylene carbonate content, its wettability gradually improves; with the increase of LiPF6 content, its wettability gradually improves. From the above data, it can be seen that different electrolyte formulas have different wettability on the positive electrode. Further experimental design and detailed comparative tests can quickly find the optimal combination.

[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A device for testing the wettability of lithium ion electrolyte and battery materials, characterized in that: The invention comprises a test stand and a burette, wherein the burette can be fixed on the test stand, a surface vessel for placing a test substrate is provided below the burette, the burette is used to drip the electrolyte to be tested onto the test substrate, and also comprises a timer for recording the infiltration time after the electrolyte to be tested is dripped onto the test substrate; an angle measuring device and a graduated needle are also provided on the test stand, when the graduated needle points to the outermost part of the electrolyte, the angle value corresponding to the graduated needle can be read by the angle measuring device; the angle measuring device is a semicircular protractor with a scale, the center of the protractor is fixed on the stand and coincides with the central axis of the burette, the fixing height of the burette on the test stand is consistent with the center height of the angle measuring device, and the graduated needle is fixed at the center of the protractor and can rotate around the center of the protractor.

2. The device for testing the wettability of lithium ion electrolyte and battery materials according to claim 1, characterized in that: The surface vessel is a flat glass vessel.

3. A method for testing the wettability of lithium ion electrolyte and battery materials, based on the device for testing the wettability of lithium ion electrolyte and battery materials according to any one of claims 1 to 2, characterized in that: The following steps are involved: The prepared positive electrode, negative electrode or separator is cut into sheet samples as test substrates, and electrolytes of different formulations are prepared according to different solvent ratios as the electrolytes to be tested; Use a burette to absorb the electrolyte to be tested, and fix the burette on a test stand; place the test substrate on a surface vessel located below the burette, and adjust the fixed height of the burette on the test stand so that the distance between the lower end of the burette and the upper surface of the test substrate is 0.5CM to 3CM; 1 to 5 drops of the electrolyte to be tested are dripped onto the test substrate through the burette, and timing starts from the time when the electrolyte to be tested is dripped. After a preset time, a scale needle is pointed to the outermost edge of the electrolyte, and the angle value corresponding to the scale needle is read through an angle measuring device; the wetting radius is calculated using a sine formula based on the measured angle value corresponding to the scale needle and the fixed height of the burette on the test bracket.

4. The method for testing the wettability of lithium ion electrolyte and battery materials according to claim 3, characterized in that: When making the test substrate, electrode sheets with different compaction densities or different thicknesses are selected for the positive and negative electrodes. The positive electrode sheets are vacuum baked at 100℃-120℃ and the negative electrode sheets are vacuum baked at 80℃-100℃ for 6-8 hours, then cooled to 40℃-60℃ and cut into 2cm*2cm sheet samples for use as test substrates.

5. The method for testing the wettability of lithium ion electrolyte and battery materials according to claim 3, characterized in that: When making the test substrate, the diaphragm selects samples of different surface densities, different thicknesses, different manufacturers or different processes, vacuum bakes them at 60℃-80℃ for 1-4 hours, cools down to 40℃-60℃, and cuts them into 2cm*2cm sheet samples as test substrates for standby use.

6. The method for testing the wettability of lithium ion electrolyte and battery materials according to claim 3, characterized in that: The humidity of the test environment is less than 80%.

7. The method for testing the wettability of lithium ion electrolyte and battery materials according to claim 3, characterized in that: Repeat the test at different ambient temperatures.

Citation Information

Patent Citations

  • Non-aqueous electrolyte secondary cell and method for producing same

    CN101009392A

  • Method for measuring wettability of lithium battery electrolyte or lithium ion battery electrolyte on battery material

    CN102866084A

  • Device for measuring wetting property of battery electrolyte to battery material

    CN202421021U

  • Equipment for testing wettability of lithium ion electrolyte and battery material

    CN210834566U

  • Gravity-type slope (angle) measurer

    CN2514312Y